Knyazyeva A., Medvid O. M. Тranslation aspect of gender markers (on the material of political leaders speeches) - Knyazyeva A.; Medvid O. M. (Philological Treatises, 2020)
The article deals with the problem of political leaders verbal behaviour, touches upon its gender aspect, its feminine and masculine linguistic categories functioning. Gender speech markers include both typological lexico- stylistic aspects and specific, authorized, cultural lexico-specific features that should be reflected in translation.